2020
DOI: 10.1371/journal.pone.0235841
|View full text |Cite
|
Sign up to set email alerts
|

The source attribution analysis revealed the prevalent role of poultry over cattle and wild birds in human campylobacteriosis cases in the Baltic States

Abstract: The reservoir and source of human campylobacteriosis is primarily considered to be poultry, but also other such as ruminants, pets and environmental sources are related with infection burden. Multilocus sequence typing is often used for Campylobacter epidemiological studies to determine potential sources of human infections. The collection of 420 Campylobacter jejuni isolates with assigned MLST genotype from poultry (n = 139), cattle (n = 48) and wild birds (n = 101) were used in source attribution analysis. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
(78 reference statements)
0
18
0
1
Order By: Relevance
“…Poultry has been reported as the main source of human infection in studies carried out in different locations including Denmark ( Joensen et al, 2020 ), Sub-Saharan Africa ( Gahamanyi et al, 2020 ), or Lithuania ( Ramonaite et al, 2017 ). On the other hand, other authors have identified as important sources of human infection both chicken and ruminants in France ( Berthenet et al, 2019 ), the United States ( Kelley et al, 2020 ), Israel ( Rokney et al, 2018 ), and Sub-Saharan Africa ( Hlashwayo et al, 2020 ) or chicken and wild birds in Baltic countries ( Mäesaar et al, 2020 ). Moreover, the detection of no major differences in the resistance profiles among isolates from different points of the chicken meat processing chain ( Dramé et al, 2020 ) suggests that AR spread is originated on upstream steps, such as the animal feeding, where the animals are exposed to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Poultry has been reported as the main source of human infection in studies carried out in different locations including Denmark ( Joensen et al, 2020 ), Sub-Saharan Africa ( Gahamanyi et al, 2020 ), or Lithuania ( Ramonaite et al, 2017 ). On the other hand, other authors have identified as important sources of human infection both chicken and ruminants in France ( Berthenet et al, 2019 ), the United States ( Kelley et al, 2020 ), Israel ( Rokney et al, 2018 ), and Sub-Saharan Africa ( Hlashwayo et al, 2020 ) or chicken and wild birds in Baltic countries ( Mäesaar et al, 2020 ). Moreover, the detection of no major differences in the resistance profiles among isolates from different points of the chicken meat processing chain ( Dramé et al, 2020 ) suggests that AR spread is originated on upstream steps, such as the animal feeding, where the animals are exposed to antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Although various animal species, including wild birds, are known sources of Campylobacter infection ( Zenebe et al, 2020 ; Mughini-Gras et al, 2021 ), poultry is accepted to act as reservoirs of 50–80% of Campylobacter infections in humans, and cattle are considered to act as reservoirs of 20–30% of human infections ( European Food Safety Authority [EFSA], 2010 ). One study conducted in the Baltic States showed that clinical cases of Campylobacter jejuni ( C. jejuni ) infections in humans were associated with sources from poultry (88.3%), cattle (9.4%), and wild birds (2.3%) ( Maësaar et al, 2020 ). Another study that used multilocus sequence typing (MLST) to determine the infection source linked 64.5% of human C. jejuni infection to poultry, with cattle and wild birds accounting for 25.8 and 2.3%, respectively ( Levesque et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over 95 million people infected with foodborne diseases were found to be linked with Campylobacter globally in 2010 [ 1 ], and an estimated 1.5 million people get infections with these pathogens each year in the United States [ 2 , 3 ]. The food animals: for example poultry, cattle, sheep, pigs, and ostriches; pets, including dogs and cats; and environmental sources, are associated with human campylobacteriosis [ 4 ]. As enteric and zoonotic pathogens, some Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…As enteric and zoonotic pathogens, some Campylobacter spp. are well adapted as a commensal in the intestinal tract of various food-producing animals, like ruminants and poultry [ 5 ], and act as a reservoir of Campylobacter [ 4 ].…”
Section: Introductionmentioning
confidence: 99%